Sturm-Liouville problems : theory and numerical implementation - Guenther, Ronald B.; Lee, John W., 1942- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Sturm-Liouville problems arise naturally in solving technical problems in engineering, physics, and more recently in biology and the social sciences. These problems lead to eigenvalue problems for ordinary and partial differential equations. Sturm-Liouville Problems: Theory and Numerical Implementation addresses, in a unified way, the key issues that must be faced in science and engineering applications when separation of variables, variational methods, or other considerations lead to Sturm-Liouville eigenvalue problems and boundary value problems.
3.6.3 Spectral Properties of Kellogg Kernels3.7 Singular Kellogg Kernels; 3.7.1 Compound Kernels; 3.7.2 Spectral Properties of Compound Kernels; 3.7.3 Spectral Properties of Kellogg Kernels; 4. Regular Sturm-Liouville Problems; 4.1 Sturm-Liouville Form; 4.2 Sturm-Liouville Differential Equations; 4.3 Initial Value Problems; 4.3.1 Basis of Solutions; 4.3.2 Variation of Parameters; 4.3.3 Continuous Dependence; 4.4 BVPs and EVPs -- Examples; 4.5 BVPs and EVPs -- Notation; 4.6 Green's Functions; 4.6.1 Separated Boundary Conditions; 4.6.2 Mixed Boundary Conditions; 4.7 Adjoint Operators and Problems
OCLC-licensed vendor bibliographic record.
Keywords: Sturm-Liouville equation; Differential equations; Eigenvalues; MATHEMATICS / Calculus; MATHEMATICS / Mathematical Analysis; MATHEMATICS / Applied; MATHEMATICS / Differential Equations; MATHEMATICS / Geometry / General